'Enteroglucagon': A specific effect on gastric glands isolated from the rat fundus. Evidence for an 'oxyntomodulin' action. Issue 2 (February 1981) - Bataille, D.; Gespach, C.; Coudray, A. M.; Rosselin, G.
Abstract : A newly isolated porcine glucagon-like biologically active intestinal peptide ('enteroglucagon') has been tested for its ability to stimulate the cyclic AMP system present in different tissue preparations from the rat: membranes prepared from liver or from isolated fundic glands as well as intact glands isolated from either the fundus or the antrum. Enteroglucagon (EG) was about l0 times less potent than pancreatic glucagon (G) in liver membranes, whereas it was about 20 times more potent than G in fundic membranes as well as in fundic glands, where it acts at doses as low as 3 × 10 −10 M. EG and G were practically ineffective in antral glands. It is concluded that EG is an 'under-glucagon' in rat liver, whereas it is a 'super-glucagon' in rat fundic glands. Accordingly, we propose to call this peptide 'oxyntomodulin'.